19. THE EFFICIENCY IN INCREASING THE USE OF DOMESTIC DRUGS SUBJECT TO INSURANCE PAYMENT HEALTH AT PUBLIC HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Objective: The evaluate the effectiveness of Circular 10/2016/TT-BYT in increasing the use ofdomestically produced modern drugs within the coverage of the health insurance fund in publichospitals in Vietnam.Subjects and methods: In the intervention study, the subject was the list of new drugs under thepayment scope of the Health Insurance fund used at public hospitals 3 times in 2017, 2018, and 2019.Result: The number of domestic drug items under Circular 10 in 2018 (858 items) and 2019(821 items) increased compared to 2017 (809 items), but the ratio of domestic drug items in 2017was higher than the rate of domestic drug items in 2018, 2019, the difference was not statisticallysignificant (p > 0.05).Conclusion: Circular 10 has had a specific impact in promoting the substitution of some foreigndrugs with domestic ones that meet the treatment requirements, drug prices and supply capacity.
Keywords: Circular 10, Domestic drugs.